Toxicity effects of curcumin analogue, 2, 6-BIS (2-fluorobenzylidene) cyclohexanone on zebrafish (Danio rerio F. Hamilton, 1822) - Nazarudin, Nur Amiza (2017)
Non-steroidal anti-inflammatory drugs (NSAIDs) have been used to reduce pain and treat inflammatory diseases such as Rheumatoid Arthritis and Alzhemeir’s Disease. However, treatment with NSAIDs has been associated with significance side effects towards heart diseases in humans and experimental animals in long terms. Our previous study has shown that curcumin analogue, 2,6-bis(2- fluorobenzylidene)cyclohexanone (MS65) demonstrated strong anti-inflammatory activity in cellular model. Thus, in the present study the toxicity effects of newly synthesized curcumin analogue (MS65) was determined on zebrafish (Danio rerio) as an animal model. The toxicity effects of MS65 compound were evaluated by measuring survival rate and recording heartbeat of zebrafish embryos from day 0 to day 5, observing the morphological defects in developing zebrafish embryos, investigating the cardiac defects on 72 hours postfertilization of zebrafish larvae via fluorescence immunostaining and observing the toxicity effects on adult zebrafish kidney and intestine via histopathology. The toxicity effects of curcumin, celecoxib and aristolochic acid (AA) were also carried out for comparison. The LC50 value of survival rate for MS65 compound on zebrafish embryos were 12.5 µM. The heart rate of zebrafish larvae recorded at 5 day of exposure to 6.25 µM of MS65 was 131 ± 0.15 min-1 . The morphological defect result showed pericardial edema toward zebrafish embryos after treated with 6.25 µM of MS65. MF20 Monoclonal antibody stained uniformly in the heart of MS65- treated zebrafish larvae and showed normal size of the heart. In contrast, MF20 staining in AA-treated zebrafish larvae showed a more intense pattern and highlighted the small size of the heart. Histological analysis reveals that MS65-treated adult zebrafish displayed less necrosis in kidney and low level of erosion in intestine. The results demonstrated that MS65 compound showed low toxicity effects toward zebrafish model compared to celecoxib, an NSAID and AA, a toxic compound that caused heart failure in zebrafish embryos. As a conclusion, the ii present study indicated that the newly synthesized curcumin analogue, MS65 has low toxicity effects towards zebrafish model and could be pharmacologic potential drug in the treatment of diseases with low toxicity effects.